Analisis Strategi Penanganan Keluhan dan Kepuasan Konsumen pada Toko Lantikya Store Jombang - Siti Munawaroh; Sri Yuni Wulandari (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2023)
Complaint is a feedback or feedback given by consumers for the service they have received. Complaints given by consumers usually arise from dissatisfaction with the services provided by company or agency employees. Satisfaction is someone's pleasure or disappointment that occurs after a comparison of product performance is set based on expected performance. Lantikya store is a store engaged in the sale of office stationery items (ATK), galleries, accessories, baby shops, children's toys, and many more. Lantikya Store often finds consumer complaints in the form of unsatisfactory service and empty items that consumers are looking for. Sales assistants at the Lantikya store have their own way of dealing with consumer complaints, while this research was conducted to analyze the strategies employed by the Lantikya store employees when they received complaints, as well as benchmarks for consumer satisfaction. The method used in this research is descriptive qualitative research method. The results of this research are data obtained from several strategies carried out by employees of the Lantikya store when they find consumer complaints, namely listening, apologizing and providing solutions to these consumers. As well as measuring consumer satisfaction can be seen from its loyalty.